Insecticidal Activity of Extracts and Fractions of the Anting-Anting Plant (Acalypha indica) with Variations in Drying Methods Against Aedes aegypti Mosquitoes - Ari Widiyantoro; Muhammad Akib Yuswar; Raden Roro Erni Kusuma Putri (Poltekkes Kemenkes Surabaya, 2024)
The Anting-Anting plant (Acalypha indica) is a shrub commonly used by the indigenous people of West Kalimantan as a mosquito repellent. This study aims to reveal the insecticidal capabilities of extracts and fractions from the leaves and roots of the Anting-Anting plant (Acalypha indica) with and without drying. Previous research has shown that the leaves of the Anting-Anting plant exhibit insecticidal activity against Aedes aegypti larvae. The extracts used were only water and methanol extracts, obtained through various extraction processes, but no publication has yet addressed the insecticidal activity of the roots with different drying methods. This study used samples of the leaves and roots of the Anting-Anting plant, differentiated by oven drying at 40°C, air drying, and no drying. Extraction was performed through maceration using methanol as the solvent, followed by liquid-liquid partitioning using n-hexane, dichloromethane, and ethyl acetate solvents. The active fractions with the highest insecticidal activity were analyzed for phenolic and flavonoid content. The results showed that the ethyl acetate fraction from the air-dried roots of the Anting-Anting plant could kill 100% of the larvae at a concentration of 40 ppm. Phytochemical tests indicated that the ethyl acetate fraction from the air-dried roots contained alkaloid, phenolic, and flavonoid compounds. Based on the analysis of phenolic and flavonoid content in the ethyl acetate fraction of the air-dried roots, the values were found to be 79.75±0.23 mg GAE/g and 68.45±0.41 mg QE/g, respectively. This indicates that the air-dried roots of the Anting-Anting plant have the potential to be an insecticide against Aedes aegypti.